2001
DOI: 10.1086/323474
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Tertiary Radiations of Fabaceae in the Greater Antilles: Alternatives to Cladistic Vicariance Analysis

Abstract: The fossil record shows that the legume family was abundant and taxonomically diverse in Early Tertiary tropical deciduous forests of North America. Today, woody members of this family are almost nonexistent in temperate deciduous forests. This former North American legume diversity now lies in the Tropics, including the Greater Antilles. To show the Antillean refugia, we detail a phylogenetic and biogeographic analysis of two legume groups, the Ormocarpum and Robinia clades, which have either a Tertiary fossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 56 publications
3
30
1
2
Order By: Relevance
“…This hypothesis is also congruent with the biogeographical history of Central American and Andean Polystichum proposed by Driscoll and Barrington (2007) as well as McHenry and Barrington (2014), who suggested that the Neotropical clade has a northern origin, and that the Andean Polystichum lineage originated from a boreotropical Mexican ancestor. A similar biogeographical pattern has been proposed for other boreotropical fern (e.g., Nephrolepis: Hennequin et al, 2010;Diplazium: Wei et al, 2015), as well as angiosperm taxa (Fabaceae: Lavin et al, 2001; Malpighiaceae: Davis et al, 2002;Sapotaceae: Smedmark and Anderberg, 2007; Rubiaceae: Antonelli et al, 2009;Annonaceae: Erkens et al, 2009). Here the boreotropical scenario is supported by several Northern Hemisphere fossils dating back to the early Paleogene indicating an ancient occurrence in regions viewed as former boreotropical provinces.…”
Section: Early Diverging Clades In Polystichoid Ferns: Evidence For Bsupporting
confidence: 69%
See 1 more Smart Citation
“…This hypothesis is also congruent with the biogeographical history of Central American and Andean Polystichum proposed by Driscoll and Barrington (2007) as well as McHenry and Barrington (2014), who suggested that the Neotropical clade has a northern origin, and that the Andean Polystichum lineage originated from a boreotropical Mexican ancestor. A similar biogeographical pattern has been proposed for other boreotropical fern (e.g., Nephrolepis: Hennequin et al, 2010;Diplazium: Wei et al, 2015), as well as angiosperm taxa (Fabaceae: Lavin et al, 2001; Malpighiaceae: Davis et al, 2002;Sapotaceae: Smedmark and Anderberg, 2007; Rubiaceae: Antonelli et al, 2009;Annonaceae: Erkens et al, 2009). Here the boreotropical scenario is supported by several Northern Hemisphere fossils dating back to the early Paleogene indicating an ancient occurrence in regions viewed as former boreotropical provinces.…”
Section: Early Diverging Clades In Polystichoid Ferns: Evidence For Bsupporting
confidence: 69%
“…Cooling of the climate and tectonic movements during the early Oligocene led to the fragmentation of the boreotropical belt, and the migration of paratropical elements southward to tropical refuges, such as southwest China, Southeast Asia, Central America, and Mexico (Morley, 2003;Zachos et al, 2001). Whereas a boreotropical migration pattern has been identified in many angiosperm groups (e.g., Fabaceae: Lavin et al, 2001; Malpighiaceae: Davis et al, 2002;Sapotaceae: Smedmark and Anderberg, 2007; Rubiaceae: Antonelli et al, 2009;Annonaceae: Erkens et al, 2009), only a few fern studies invoked boreotropical connections as an explanation for intercontinental disjunctions (e.g., Nephrolepis Schott, Hennequin et al, 2010; Asplenium L., Schneider et al, 2004a; Diplazium Sw., Wei et al, 2015). Therefore, the boreotropical hypothesis should be carefully tested when reconstructing biogeographical scenario in ferns.…”
Section: Introductionmentioning
confidence: 99%
“…As a concrete example, different names have been used for same legume taxa in successive papers published by Matt Lavin and collaborators. Hence, TreeBASE study S754 (Lavin et al 2001) includes names such as Coursetia heterantha and C. weberbaueri. However, in Study S813 (Lavin et al 2002) these taxa were moved to the genus Poissonia.…”
Section: Name Changes In Legumesmentioning
confidence: 99%
“…If the authors and publishers are considering a second edition of this volume, this chapter might usefully be replaced by an account of exciting new studies where dated fossils can be used to assign minimum ages to nodes in molecular phylogenies of extant plants (e.g. Bremer, 2000; Lavin et al, 2001). New techniques, which need not assume that DNA substitution have been clock-like (Sanderson, 1997(Sanderson, , 2002, can use these calibrations to infer dates of all nodes in a molecular phylogenetic tree, thereby providing an indication of the age of events that have not been recorded in the fossil record.…”
Section: A J Richardsmentioning
confidence: 99%